Identification of maternal serum biomarkers for prenatal diagnosis of nonsyndromic orofacial clefts. Issue 1 (24th December 2021) - Wang, Xinhuan; Yang, Xiaohong; Huang, Pei; Meng, Xiujiao; Bian, Zhuan; Meng, Liuyan
Abstract: Nonsyndromic orofacial clefts (NSOFCs) are the most common congenital defects in the oral and maxillofacial regions. It is mainly diagnosed prenatally through fetal ultrasonography. However, the accuracy of ultrasonography for NSOFC is unreliable. Maternal serological screening is a noninvasive method for the diagnosis of fetal malformations. In our study, we sought to identify specific biomarkers in maternal serum for predicting NSOFC prenatally. We quantified the alterations in maternal serum protein profiles between 20 pregnant women with NSOFC fetuses and 20 pregnant women with healthy fetuses by using isobaric tags for relative and absolute quantitation‐based mass spectrometry (MS). The serum levels of 75 elevated and 50 decreased proteins in the NSOFC group were detected. Twenty‐eight candidate biomarkers were selected for further confirmation by multiple reaction monitoring‐MS; of these, 16 proteins were found to be significantly different. More importantly, the levels of three proteins (APOA, HPT, and CRP) were verified by ELISAs to be obviously altered in serum from pregnancies carrying fetuses with NSOFC. Our results indicate that analysis of the maternal serum proteome is a feasible strategy for biomarker discovery of NSOFC, and APOA, HPT, and CRP proteins are potential serum biomarkers for prenatal diagnosis of NSOFC. Abstract : Nonsyndromic orofacial clefts (NSOFCs) are the most common congenital defects in the oral and maxillofacial regions. It is mainly diagnosed prenatally through fetal ultrasonography. However, the accuracy of ultrasonography for NSOFC is unreliable. Maternal serological screening is a noninvasive method for the diagnosis of fetal malformations. In our study, we sought to identify the specific biomarkers in maternal serum for predicting NSOFC prenatally.